2019
DOI: 10.5505/kpd.2019.04127
|View full text |Cite
|
Sign up to set email alerts
|

Two cases with avoidant/restrictive food intake disorder: Effectiveness of EMDR and CBT combination on eating disorders (eng)

Abstract: Traumatic life events are among the etiological factors that may trigger eating disorders (ED). In the present study, we examined the effects of Eye Movement Desensitization and Reprocessing (EMDR) therapy and Cognitive Behavioral Therapy (CBT) therapies combined on two young girls, who had symptoms of ED as a consequence of their traumatic experiences.Two Caucasian female patients arrived at the clinic with highly similar complaints about eating. They both were mutually holding the fear that food would get st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Only one case study related to eating disorders could be identified (Yasar et al, 2019 ). This study applied a combination of EMDR and CBT in an intermingled manner (EMDR-CBT-EMDR) to two young adult patients suffering from restrictive food intake disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Only one case study related to eating disorders could be identified (Yasar et al, 2019 ). This study applied a combination of EMDR and CBT in an intermingled manner (EMDR-CBT-EMDR) to two young adult patients suffering from restrictive food intake disorder.…”
Section: Resultsmentioning
confidence: 99%